Increasing outdoor play opportunities in the neighborhood environment through Play Streets - Larkin, Katelyn (Kansas State University, 2020)
At present, children in the United States are spending less time engaging in outdoor play than ever before. Play is extremely beneficial to a child’s health and development because it provides social, cognitive, creative, and physical development opportunities. As children become more sedentary due to lack of time, safety concerns, and lack of accessible play spaces, the prevalence of health and development issues is rising. When children are able to play outdoors, they tend to stay close to their home environment, which is preferred by parents as well, but many neighborhood environments are not suitable for children’s play. A Play Street is the temporary closure of a street, allowing for children to play close to their home, while maintaining a safe atmosphere. Safety is further reinforced by having parents from the neighborhood act as supervisors during the event. The purpose of this research was to analyze opportunities and barriers for outdoor play and determine the most suitable neighborhoods to implement Play Streets. This research also helped gain a better understanding of children’s outdoor play behaviors, patterns, barriers, and parent’s opinions on suggested Play Street locations. This information was used to complete informed design typologies for three different Play Street locations. A mixed-method approach was applied to this study. A GIS-based suitability analysis and parental surveys were used to develop informed Play Street design typologies and solutions. These techniques were used to ensure that the designed spaces would mitigate parental concerns, while maintaining a level of excitement for the children. The findings of this study could be used to assist community members, developers, policy makers, and designers in organizing Play Streets and neighborhood development.
Keywords: Play Street; Outdoor Play; Children; Neighborhood Play; Suitability; Typology